2012
DOI: 10.1089/hum.2011.166
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Disease Severity in Symptomatic,Smn−/−;SMN2+/+, Spinal Muscular Atrophy Mice Following scAAV9-SMN Delivery

Abstract: Spinal muscular atrophy (SMA), an autosomal recessive neuromuscular disorder, is the leading genetic cause of infant mortality. SMA is caused by the homozygous loss of Survival Motor Neuron-1 (SMN1). In humans, a nearly identical copy gene is present, SMN2. SMN2 is retained in all SMA patients and encodes the same protein as SMN1. However, SMN1 and SMN2 differ by a silent C-to-T transition at the 5' end of exon 7, causing alternative splicing of SMN2 transcripts and low levels of full-length SMN. SMA is monoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…administration of scAAV9–SMN, icv. administration was shown to produce a greater degree of rescue in SMA [100,107]. Similar conclusions were also drawn regarding icv.…”
Section: Smn Induction: Modes Of Action For Smn Therapeutic Strategiessupporting
confidence: 59%
See 1 more Smart Citation
“…administration of scAAV9–SMN, icv. administration was shown to produce a greater degree of rescue in SMA [100,107]. Similar conclusions were also drawn regarding icv.…”
Section: Smn Induction: Modes Of Action For Smn Therapeutic Strategiessupporting
confidence: 59%
“…Similar conclusions were also drawn regarding icv. administration in an even more severe model of disease that typically dies at approximately P5 [107]. While the extension in survival did not achieve the 150–250 days seen with the less severe model, this work demonstrated that delivery of the scA AV9-SMN vector can significantly extend survival even in severely symptomatic SMA animals.…”
Section: Smn Induction: Modes Of Action For Smn Therapeutic Strategiesmentioning
confidence: 83%
“…On the other hand, experiments conducted in Taiwanese type I SMA mice yielded variable results and less promising survival benefits with ICV administration of SMN1 sequence (Fig. 1) [82]. These findings underscore the caution that must be exercised when extrapolating the results of pre-clinical studies conducted in a specific mouse model to design clinical trials in humans.…”
Section: Gene Therapy and Trans-splicingmentioning
confidence: 99%
“…However, while intravenous injections of AAV9 vectors achieved efficient transduction of spinal motor neurons in fetal, neonate, and adult mice, as well as in adult cats and pigs [913, 15, 16], most of the transduced cells were astrocytes in adult mice and nonhuman primates [9, 14, 16]. Thus, extensive gene delivery to neurons in the adult CNS remains challenging.…”
Section: Introductionmentioning
confidence: 99%